Changes in the Auditory Association Cortex in Dementing Illnesses. Issue 10 (December 2020) - Aylward, Alana; Auduong, Priscilla; Anderson, Jeffrey S.; Zielinski, Brandon A.; Wang, Angela Y.; Weng, Cindy; Foster, Norman L.; Gurgel, Richard K.
Abstract : Objective: To evaluate the relationship between degree of cognitive impairment and gray-matter density changes in the auditory cortex. Study Design: Retrospective case-control. Patients: Six hundred sixty-three patients of a tertiary referral center cognitive disorders clinic. Intervention: Magnetic resonance imaging. Main Outcome Measures: Ratios of gray matter density of the primary auditory cortex (A1) to whole brain and auditory association cortex (AAC) to whole brain in patients with Alzheimer's disease (AD) compared with mild cognitive impairment (MCI) and patients with a mini-mental state exam (MMSE) scores ⩽25 versus >25. Results: After multivariate analysis, a statistically significant difference between AAC to brain ratios for patients with a MMSE ⩽25 (n = 325) compared with >25 (n = 269) was found, with values −0.03 (95% CI −0.04 to −0.02, p < 0.0001) on the left and −0.04 (95% CI −0.06 to −0.03, p < 0.0001) on the right. The adjusted average difference of left and right AAC to brain ratios between AD patients (n = 218) compared with MCI patients (n = 121) was also statistically significant, at −0.03 (95% CI −0.05 to −0.01, p = 0.004) and −0.05 (95% CI −0.07 to −0.03, p < 0.0001), respectively. There was no statistically significant difference in the left or right A1 to brain ratios between the MMSE groups or between the AD and MCI groups. Conclusions: The AAC for patients with MMSE ⩽25 and for those with AD shows decreased gray matter density when compared with patients with better cognitive function. No difference was detected in A1, raising the possibility that patients may have intact neural hearing, but impaired ability to interpret sounds.